Antitrypanosomal Secondary Metabolites From Soil Actinomycetes Isolated From Penang National Park - Husin, Lili Sahira (2014)
The unique ecosystems in Malaysia can be utilized as potential sources for isolating actinomycetes isolates that produce interesting bioactive secondary metabolites. This secondary metabolite exhibits a wide range of bioactivity including antitrypanosomal activity. The option of new lead compound is needed for the disease treatment that caused by the trypanosome parasite since the existing drugs to cure are very limited due to drug resistance. In this study, a total of 83 actinomycetes isolates were successfully revived from cryovials stored at -80oC in FRIM Actinomycetes Culture Collection (FACC). The isolates were grown in three different fermentation media (M1, M2, and M3) and a total of 249 culture broth extracts obtained were evaluated for in vitro antitrypanosomal assay against Trypanosoma brucei brucei strain BS221 via primary, secondary and tertiary assays. Extracts that showed strong and moderate activities were evaluated for antitrypanosomal activity in tertiary assay and cytotoxicity to determine their selectivity index (SI) values. Among the active extracts that showed good selectivity toward the trypanosoma parasite, four extracts FACC-A032-M3, FACC-A026-M3, FACC-A048-M3 and FACC-A049-M3 produced strong antitrypanosomal activity (IC50 value < 1.56 g/ml) and high selectivity (SI  20). The potential isolates were further studied for their cultural, macromorphological, physiological and biochemical characteristics and spore chain type. Isolates FACC-A032 and FACC-A026 were tentatively identified as Streptomyces sp. and isolates FACC-A048 and FACC-A049 were categorized into the non-Streptomyces group.